Sphingosine 1-Phosphate Receptor Signaling Regulates Proper Embryonic Vascular Patterning - Mendelson, Karen (American Society for Biochemistry and Molecular Biology, 2013)
Sphingosine 1-phosphate (S1P) binds G-protein-coupled receptors (S1P(1–5)) to regulate a multitude of physiological effects, especially those in the vascular and immune systems. S1P receptors in the vascular system have been characterized primarily in mammals. Here, we report that the S1P receptors and metabolic enzymes are conserved in the genome of zebrafish Danio rerio. Bioinformatic analysis identified seven S1P receptor-like sequences in the zebrafish genome, including duplicated orthologs of receptors 3 and 5. Sphingolipidomic analysis detected erythrocyte and plasma S1P as well as high plasma ceramides and sphingosine. Morpholino-mediated knockdown of s1pr1 causes global and pericardial edema, loss of blood circulation, and vascular defects characterized by both reduced vascularization in intersegmental vessels, decreased proliferation of intersegmental and axial vessels, and hypersprouting in the caudal vein plexus. The s1pr2 gene was previously characterized as a regulator of cell migration and heart development, but its role in angiogenesis is not known. However, when expression of both s1pr1 and s1pr2 is suppressed, severely reduced vascular development of the intersegmental vessels was observed with doses of the s1pr1 morpholino that alone did not cause any discernible vascular defects, suggesting that s1pr1 and s1pr2 function cooperatively to regulate vascular development in zebrafish. Similarly, the S1P transporter, spns2, also cooperated with s1pr1. We propose that extracellular S1P acts through vascular S1P receptors to regulate vascular development.